2002
DOI: 10.1097/00004872-200201000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Reduced arterial distensibility is a predictor of cardiovascular disease in patients after renal transplantation

Abstract: The distensibility of the common carotid artery is an independent predictor of cardiovascular disease in renal transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
1
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 25 publications
7
68
1
6
Order By: Relevance
“…In agreement with previous studies on ESRD patients, [3][4][5] patients with essential hypertension and diabetes, 6 -11 our present findings indicate that aortic PWV is a strong and independent predictor of CV mortality. In contrast, the PWV of peripheral conduit arteries, for both upper and lower limbs, has no prognostic value for CV mortality in ESRD patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies on ESRD patients, [3][4][5] patients with essential hypertension and diabetes, 6 -11 our present findings indicate that aortic PWV is a strong and independent predictor of CV mortality. In contrast, the PWV of peripheral conduit arteries, for both upper and lower limbs, has no prognostic value for CV mortality in ESRD patients.…”
Section: Discussionsupporting
confidence: 93%
“…[3][4][5][6][7][8][9][10][11] In contrast to aortic PWV peripheral arteries, PWV had no prognostic value in ESRD patients. Whether a similar absence of a relationship between and CV mortality is present in the general population remains to be established.…”
Section: Pannier Et Al Stiffness Of Capacitive and Conduit Arteriesmentioning
confidence: 99%
“…3 In addition, because for a given ventricular ejection aortic stiffness is the major determinant of PP, increased aortic pulse wave velocity (PWV), a classic marker of arterial rigidity, has also been identified as an independent predictor of CV risk in numerous populations. [4][5][6][7][8][9][10][11][12][13][14][15][16] Only three studies took place in the elderly; 7,13,16 none was specifically designed to test the multi-adjusted added value of aortic PWV in term of all-cause mortality prediction. Finally, very few studies addressed the potential validity of thesepathophysiological considerations in the frail oldest old with a high burden of CV disease.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, classic risk factors cannot fully explain the CV risk in this population. It is reported that the Framingham CV risk score significantly underestimates the risk of ischemic heart disease in transplant patients [66] and therefore, non-classic risk factors including C-reactive protein, homocystein and renal function as well as arterial stiffness may contribute in CV risk in this population [67,68].…”
Section: Risk In Kidney Transplanted Patientsmentioning
confidence: 98%